Frequency of Contrast-Induced Nephropathy in Patients Undergoing PCI - Muhammad Zafarullah, Gulshan Ahmad, Muhammad Suleman Khan, Muhammad Ahmad Raza Butt, Umar Farooq, Muhammad Imran Ashraf (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Contrast-induced nephropathy (CIN) is accompanied by a considerable increase in illness and death following percutaneous coronary intervention (PCI). Aim: The present work aims to detect the frequencies of patients with different risk factors that affected how much with CIN Percutaneous coronary intervention. Methodology: This is a planned distinct study that included 200 patients that received PCI at the Punjab Institute of Cardiology in Punjab, Pakistan. Regarding the baseline values, a CIN was described as a 25 percent or 0.5 mg/dl increase in serum creatinine after 48 hours following PCI. Several reliable indicators of CIN were examined in this study like patient’s demographics (age and gender), Body mass index (kg/m2), Co-morbidities and Serological parameters as well as angiographic and practical characteristics of patients. Results: Out of 200 patients, (11%) developed contrast nephropathy and the (89%) didn’t. CIN patients were found to be older, more commonly males, more likely to have Diabetes mellitus, dyslipidemia as well as Hypertension, and higher levels of peak creatine kinase and LDL (mg/dl). In the CIN group, the causative artery was found in the left anterior descending artery more frequently and the patients (100%) in the CIN group who received contrast volume > 100ml developed CIN more frequently, significantly than those without CIN (22.4%,) at p< 0.001. Keywords: Percutaneous coronary intervention, Contrast-induced nephropathy, serum creatinine, diabetes, and hypertension.